2004
DOI: 10.1111/j.1537-2995.2004.03227.x
|View full text |Cite
|
Sign up to set email alerts
|

Which factors can affect cord blood variables?

Abstract: Our data indicates that VD and heavier babies showed significant increase in TNC by multiple regression analysis. However, r(2)= 0.07 and even when all factors were considered, r(2)= 0.16, which is a percentage too insignificant to be applied for ideal CB screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
4
15
1
Order By: Relevance
“…As described by others [16], [24], [26], maternal age had no impact on the HSPC concentration. In contrast, other groups reported an influence of maternal age on HSPC concentration, which is in line with our results [19], [27]. In addition, the univariate analysis shows a maternal age-dependent influence on the clonogenic capacity.…”
Section: Discussionsupporting
confidence: 92%
“…As described by others [16], [24], [26], maternal age had no impact on the HSPC concentration. In contrast, other groups reported an influence of maternal age on HSPC concentration, which is in line with our results [19], [27]. In addition, the univariate analysis shows a maternal age-dependent influence on the clonogenic capacity.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the CB units from male babies had a high fraction of CD34+ cells/TNCs (p = 0.007); thus, CD34+ cells showed no difference according to neonate sex, although the number of TNCs was lower in males (p < 0.001). The finding that TNCs and CD34+ cells are correlated with the CB volume, gestational age, and birth weight is consistent with previous studies 9,10,13‐15,19 . CD34+ cells/TNCs showed a positive correlation with the CB volume and birth weight and a negative correlation with gestational age.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have been reported regarding the maternal and neonatal factors that could affect hematopoietic variables of CB units such as TNCs and CD34+ cells 9‐16 . To advance the CB banking process in Korea, which comprises a unique population different from western countries, 17 the impact of maternal and neonatal factors on hematopoietic variables of CB should be clarified.…”
mentioning
confidence: 99%
“…Our results confirm the relationship between infant and placental weight and cord blood volume and cell content, a finding also reported by others [6,16,17,18,19]. In fact, placental weight was the only variable that independently influenced volume, TNC, CD34+ cells and CFU content of collections.…”
Section: Discussionsupporting
confidence: 80%